Optimization Algorithms for Cable Fault Localization and Assessment in Smart Power Systems - Wenxuan Wang; Yali Shi; Minghui Liu (IEEE Access)
Frequency domain reflection (FDR) has good detection and localization ability for defects or faults with weak impedance changes, and has been widely used in the field of cable fault diagnosis, however, in recent years, field experience has shown that this method cannot solve the problem of judging the fault type and severity yet. In view of the above problems, this paper proposes an optimization algorithm based on the frequency domain-space domain integral transform to enhance the cable fault location capability and assess the fault type and severity. Firstly, we use the good self-sustainability of the optical soliton (Soliton) in fiber optic communication to modulate its spectral information into the reflection information of the cable frequency domain, secondly, we define the attenuation operator to compensate for the attenuation of the spectral information and the integral kernel function, and set up the Chebyshev window function to weaken the low-frequency components of the spectrum to be detected. This method realizes the identification of impedance mismatch type at the cable anomaly while ensuring high detection sensitivity and localization accuracy, and further evaluates the fault severity according to the amplitude of reflected information in the localization curve. The simulation verification of inductive and capacitive faults and intermediate joints with different mismatches is carried out in 10 kV cable simulation lines; the actual measurements are carried out on coaxial cables, 10 kV cable experimental lines, and 5 km of 110 kV cable lines that have been put into operation, respectively, and the results show that the error of its localization accuracy is less than 2%, which enables it to accurately determine the type of faults and assess the seriousness of the faults.